Biochar-based materials for electroanalytical applications: An overview - Yuhong Zheng; Chaoguang Yu; Li Fu (Green Analytical Chemistry, 2023)
Biochar-based materials, derived from renewable biomass resources, have emerged as promising candidates for electroanalytical applications due to their unique physicochemical properties, such as high surface area, excellent biocompatibility, and good chemical stability. This review provides a comprehensive overview of recent advancements in the development and application of biochar-based materials in electrochemical devices, including sensors, energy storage, and catalysis. We discuss the synthesis and functionalization of biochar materials, focusing on the effects of feedstock and pyrolysis conditions on their properties. The applications of biochar-based materials in electrochemical devices are reviewed, with a particular emphasis on enzyme-based biosensors, DNA-based biosensors, and immunosensors. Despite their promising performance, challenges such as reproducibility, electrical conductivity, and long-term stability need to be addressed to facilitate their widespread adoption in the industry. We also discuss emerging trends, such as the development of multifunctional hybrid materials and integration into flexible devices. Finally, we highlight the importance of policy, regulatory aspects, and environmental assessments to ensure the safe and sustainable use of biochar-based materials in electroanalytical applications.